Budaya Keselamatan dan Model Kepemimpinan Keselamatan Dalam Menjamin Terwujudnya Motivasi Keselamatan Pelayaran KapalKapal Niaga dengan Moderasi Sistem Manajemen Keselamatan (ISM Code) - Hero Budi Santoso; Prijantono Dillyanto (Jurnal Maritim Polimarin, 2020)
The sea transport’s that guarantees the safety of shipping for commercial ships requires a well-integrated ship operation management system, to minimize the risk of hazards that can be arise such as sunken ship, collisions, aground, fires on board. The safety management system (SMK3) can be used as a way to prevent work accidents caused by worker behavior through a safety culture. Required all parties concerned, to implement of the ISM Code is intended to generate and maintain safety motivation in safety concern in shipping industry. Scope of problem in this study is to measure the influence of safety culture aspects and safety leadership on safety motivation in the shipping industry, especially safety behavior on ships. This study aims to determine the effect of safety culture and safety behavior on work safety (safe operation) on commercial ships. Results of this research can be produce solutions to reduce the number of ship accidents on both national and international shipping. The type of research in this study is correlational research.and empirical study that proof the influence of safety culture, safety leadership and safety motivation on shipping workers, as formulated in the hypothesis. The processed data obtained through data collection in the form of a questionnaire. The data analysis technique used is the instrument quality test, regression analysis, fit model test and hypothesis testing. The results of the recommendations that researchers propose are, increasing the implementation of safety culture in shipping companies, regular training to improve safety management at the company level and training in safety leadership models need to be improved in the shipping sector.